Standards of impartiality of the prosecution in the sense of Article 9 (part 2) of the Criminal Procedure Code (CPC) of Ukraine: value and criteria - Глинська , Н. В. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2017)
The article is devoted to the problem of normative and substantive content of the standard of impartiality of investigation by the investigator, the prosecutor of the circumstances of criminal proceedings. Objective investigation is one of the necessary conditions for a fair trial in the sense given by the European Convention on Human Rights and its enforcement. Due to estimated nature of the category of impartiality, the CPC does not provide a comprehensive list of its criteria. The analysis of law enforcement practice, in particular, the justification of investigating judges procedural decisions about challenges of the investigator and the prosecutor, indicates that such circumstances may be: the illegal actions of the prosecution participators during the pre-trial investigation; ignoring the demands of the defence participators, creating obstacles for the realization of the rights of defence, numerous violations of the law requirement about three-day term to consider the petition of the defence participator in accordance with article 220 of the CPC and to take one of the procedural decisions, prescribed by law, etc. The article considers only on several most commonly known on practice facts of the prosecution participator activities, which are negatively evaluated by the defence participators (defined as manifestations of investigator and prosecutor impartiality). These include, in particular, the facts of repeated prosecution participator acts or procedural decisions, such as: appeal from the same reasons to a court with a petition for the removal of a suspect from a position and applying a preventive measure; ignoring applications of individuals and / or legal person to recognize them as victims in criminal proceedings; ignoring the petition of the defence regarding the return of the temporary Take-Over Property, that hasn’t been seized by investigating judge.

У статті розглянуто нормативний та сутнісний зміст стандарту неупередженості дослідження обставин кримінального провадження слідчим, прокурором. Автором акцентовано увагу на значенні об’єктивного підходу сторони обвинувачення при реалізації своїх повноважень на досудовому розслідуванні та критеріях стандарту неупередженості в царині кримінального провадження.
СТАНДАРТ НЕУПЕРЕДЖЕНОСТІ СТОРОНИ ОБВИНУВАЧЕННЯ В РОЗУМІННІ Ч. 2 СТ. 9 КПК УКРАЇНИ : ЗНАЧЕННЯ ТА КРИТЕРІЇ
Keywords: standard; impartiality; criteria of impartiality; objectivity of the prosecution side.; стандарт; неупередженість; критерії неупередженості; об’єктивність сторони обвинувачення.